An assessment of the effect of surface topography on coefficient of friction for lubricated non-conformal contacts - Prajapati, Deepak K.; Hansen, Jonny; Björling, Marcus (Frontiers in Mechanical Engineering, 2024)
Determining an accurate state of lubrication is of utmost importance for the precise functionality of machine elements and to achieve elongated life and durability. In this work, a homogenized mixed-lubrication model is developed to study the effect of surface topographies on the coefficient of friction. Various measured real surface topographies are integrated in the model using the roughness homogenization method. The shear-thinning behavior of the lubricant is incorporated by employing the Eyring constitutive relation. Several Stribeck curves are generated to analyze the effect of roughness lays and root mean square (RMS) roughness on the coefficient of friction. The homogenized mixed lubrication model is validated against experimental rolling/sliding ball-on-disc results, and a good agreement between simulated and experimental coefficient of friction is found.